Considerations about School Management at IF Goiano: Institutional Development Plan and Democratic Participation (CIPEEX, 2025)
School management plays a crucial role in achieving educational goals, and democratic principles are essential for its effectiveness. This study analyzes the democratic management framework within the Instituto Federal de Educação, Ciência e Tecnologia Goiano (IF Goiano), Brazil, focusing on the role of its Institutional Development Plan (Plano de Desenvolvimento Institucional - PDI) in fostering community participation. This qualitative research employs bibliographic and documentary analysis, examining the 2019-2023 PDI and related institutional documents alongside Brazilian educational legislation and theoretical frameworks. The results demonstrate that the PDI is a strategic instrument for guiding democratic management, emphasizing transparency, accountability, and the active inclusion of the academic community in decision-making processes. Key mechanisms include the Superior Council (Conselho Superior) and the College of Leaders (Colégio de Dirigentes), which aim to bridge the geographical distance between the central administration and the dispersed campuses. The study concludes that democratic management, as structured by the PDI, is a priority for IF Goiano, aligning with national legal guidelines and contributing to educational quality and equity. The findings have implications for other educational institutions under the Brazilian Ministry of Education's regulations.
Keywords: Institutional Development Plan; School Community Participation; Democratic Management; Federal Institute of Education.